2014
DOI: 10.1590/0001-3765201420130226
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of morpho-agronomic and climatic variables in successive agricultural years provides novel information regarding the phenological cycle of Jatropha in conditions of the Brazilian cerrado

Abstract: Phenological studies can provide information that enables the understanding of the dynamics of plants and how these dynamics are related to the biotic and abiotic environment. In order to study the phenological phases of Jatropha during two agricultural years, agronomic and climatic variables, such as temperature and rainfall, were evaluated. Data for each variable in each year and each genotype were subjected to analysis of variance (ANOVA) and the differences were tested at 5% probability by F test. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Genotype CNPAE-102 produces on average 130% more green fruits than genotype CNPAE-169 (Domiciano et al, 2014). However, the data of this study also indicates that A in both genotypes is broadly equivalent under field conditions, assuming that the number of green fruits in the labeled branches can be considered as a yield indicator (Laviola et al, 2012) and that CNPAE-102 has been previously shown to be more productive than CNPAE-169.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…Genotype CNPAE-102 produces on average 130% more green fruits than genotype CNPAE-169 (Domiciano et al, 2014). However, the data of this study also indicates that A in both genotypes is broadly equivalent under field conditions, assuming that the number of green fruits in the labeled branches can be considered as a yield indicator (Laviola et al, 2012) and that CNPAE-102 has been previously shown to be more productive than CNPAE-169.…”
Section: Resultsmentioning
confidence: 57%
“…Although the number of inflorescences and flowers tracked A (Figures 1 and 2), it is unlikely that there is a cause-effect relationship because of the moderate negative correlation that occurred between A and the number of green fruits on labeled branches for this same genotype (Table 2). Previous studies (Domiciano et al, 2014) showed that the number of green fruits and the number of inflorescences and flowers are genuinely correlated, suggesting the correlation between flower traits and A is spurious.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations